A 300A Dynamic Electronic Load Based On Modified Buck+boost Interleaved Converter - de Seixas, Falcondes J. M.; de Seixas, Claudiner M.; Canesin, Carlos A. (Eletrônica de Potência, 2006)
This paper presents a novel DC dynamic electronic load applied at load regulation tests of switching-mode power supplies, operating at highcurrent levels. The proposed device is based on the use of a modified Buck+Boost interleaved converter, without the use of the boost diodes, and the output filters (capacitors). Therefore, the electronic load circuitry is very simple, effective and capable to provide high pulsedcurrent levels, featuring faster rise/fall times for transient testing on high speed DC to DC converters and DC power supplies. A prototype was implemented, in order to validate the proposed structure, operating at 10V-20V DC input voltage range, 190A-290A amplitude range of the input pulsed-current (nominal value is equal to 240A±20%), with adjustable pulse-width between 4ms (adjustable time-period of 200ms) until 6ms (adjustable time-period of 350ms). The main experimental results, obtained from the implemented prototype, are presented in order to demonstrate the feasibility of the proposed dynamic electronic load, which is capable of performing experimental tests of transient load regulation for switching-mode power supplies.